Pengaruh Komunikasi Interpersonal Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Di UMKM Universal Kabupaten Tulungagung - Shafa Labiba; Eka Farida; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the effect of interpersonal communication and work environment on job satisfaction in Universal UMKM. The data used in this study used primary data obtained from interviews, observations and questionnaires and secondary data obtained from documentation. The population of this study were all Universal UMKM employees, while the sample in this study was 40 respondents. The analytical method used in this study is multiple linear analysis by testing the hypothesis using the F test and t test. The research shows that interpersonal communication and the work environment simultaneously have a positive and significant effect on job satisfaction. While partially interpersonal communication has a positive and significant effect on job satisfaction. The work environment has a positive and significant effect on job satisfaction. Keywords: Interpersonal Communication, Work Environment, and Job Satisfaction